Risk of diabetes in HIV‐infected patients is associated with cirrhosis but not with chronic HCV coinfection in a French nationwide HIV cohort. Issue 3 (14th June 2018) - Provoost, A.; Dramé, M.; Cotte, L.; Cuzin, L.; Garraffo, R.; Rey, D.; Raffi, F.; Poizot‐Martin, I.; Pugliese, P.; Bani‐Sadr, F.; ,
Summary: Background: Both human immunodeficiency virus (HIV) and hepatitis C virus (HCV) infections have been reportedly associated with a higher risk of diabetes mellitus (DM) but results are conflicting. Aims: To determine whether there is an association between chronic HCV and the incidence of DM, and to study the role of factors such as cirrhosis, IFN‐based HCV therapy, sustained virologic response (SVR) and chronic HBV infection among patients living with HIV (PLHIV) followed in a large French multicentre cohort in the combination antiretroviral therapy (cART) era. Methods: All PLHIV followed up in the Dat'AIDS cohort were eligible. Cox models for survival analysis were used to study the time to occurrence of DM. Results: Among 28 699 PLHIV, 4004 patients had chronic HCV infection. The mean duration of HCV follow‐up was 12.5 ± 8.1 years. The rate ratio of DM was 2.74 per 1000 person‐years. By multivariate analysis, increasing age, body mass index>25, AIDS status, nadir CD4 cell count ≤200/mm 3, detectable HIV viral load and cirrhosis (HR 2.26 95% CI 1.14‐1.18; P  < 0.0001) were predictors of DM, whereas longer cART duration was associated with a lower risk of DM. Chronic HCV and HBV infection and IFN‐based HCV therapy were not associated with DM. In a subanalysis among HCV‐infected patients, SVR was not related to DM. Conclusions: Our study shows that in the HIV population, cirrhosis is associated with an increased occurrence of DM, but not chronic HCV infection or duration of HCV infection. Abstract : Linked Content This article is linked to Höner zu Siederdissen and Mederacke and Provoost et al papers. To view these articles visit https://doi.org/10.1111/apt.14863 and https://doi.org/10.1111/apt.14892 .